2020
DOI: 10.1016/j.heliyon.2020.e03892
|View full text |Cite
|
Sign up to set email alerts
|

Lauric acid promotes neuronal maturation mediated by astrocytes in primary cortical cultures

Abstract: Previous studies have suggested the potential efficacy of middle chain fatty acids (MCFAs) in the treatment of mood disorders and cognitive dysfunction. MCFAs are metabolized to ketone bodies in astrocytes; however, their effects on neuronal development including neurotrophic factor level are not well-understood. In the present study, we examined the effect of MCFAs on the mRNA expression of growth factors and cytokines in primary cultures of cortical astrocytes. The effect of MCFAs on neuron-astrocyte interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It has also been reported that MCFAs increase neuronal mitochondrial biosynthesis, leading to increased brain glucose metabolism ( 100 ). In addition, the maintenance and improvement of brain function involves the promotion of neuronal regeneration and maturation, and C10:0 and C12:0 may act as agonists for these processes ( 101 ).…”
Section: Various Clinical Application Studiesmentioning
confidence: 99%
“…It has also been reported that MCFAs increase neuronal mitochondrial biosynthesis, leading to increased brain glucose metabolism ( 100 ). In addition, the maintenance and improvement of brain function involves the promotion of neuronal regeneration and maturation, and C10:0 and C12:0 may act as agonists for these processes ( 101 ).…”
Section: Various Clinical Application Studiesmentioning
confidence: 99%
“…A proof that carbon length matter is that long chain saturated fatty acids (LCSFA) as palmitate was found to stimulate inflammation in macrophages and affect microglial and astrocytic signaling pathways [ 60 , 61 ]. Also, MSCSFA as lauric acid may have beneficial effects on cognition reducing the inflammation induced by LPS in microglia [ 62 ] and regulating the production of cytokines and neurotrophic factors [ 63 ]. In our cohort, a large part of dietary SCSFA-MCSFAs derive from the consumption of dairy products such as yogurt.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the black soybean (especially fermented with P. acidilactici US1) has higher amounts of essential and non-essential amino acids that can be used as a good source for the supplementation of amino acids to improve cognitive and psychological functions. We have identified 10 fatty acid and some of them can possess anti-neuro-inflammatory and neuroprotective activity, reduce amyloidosis, and promote neuronal maturation such as α-linolenic acid, linoleic acid (26), oleic acid (27), lauric acid (28), palmitic acid (29), and stearic acid (30). Thus, fermentation of black soybean can effectively inhibit cholinesterase enzymes, inflammatory factors, oxidative stress and can potentially enhance the GABA concentration.…”
Section: Discussionmentioning
confidence: 99%